Serendipitous compositional and structural diversity in urotropine adducts of binary cadmium xanthates - Tan, Yee Seng *; Aliaa Diyana Azizuddin; Câmpian, Marius V.; Haiduc, Ionel; Tiekink, Edward R. T. * (De Gruyter, 2016)
Three new compounds, Cd(S2COMe)2(hmta) (1), Cd(S2COEt)2(hmta)0.5 (2) and Cd(S2COiPr)2(hmta) (3), have been isolated from a systematic study of adduct formation between Cd(S2COR)2, R=Me, Et and iPr, precursors and potentially polydentate hmta; hmta is urotropine (hexamethylenetetramine). The compounds have been characterised by a variety of spectroscopic techniques including a photoluminescence study in both solution and the solid-state, as well as by thermal methods. Crystallography shows 1 to have μ2-bridging hmta leading to a one-dimensional coordination polymer. This framework is essentially repeated in 2 but with a μ3-bridging hmta so that Cd(S2COEt)2 entities decorate the chain. By contrast, a binuclear zero-dimensional aggregate with terminally bound hmta is found in 3. The influence of steric bulk of the alkyl substituents in Cd(S2COR)2 is pivotal in determining the ultimate structural outcome.